Determinación del índice de calidad del agua (nsf) de la microcuenca Nagsiche ubicado en el cantón Salcedo provincia de Cotopaxi - Chicaiza Cocha, Erika Julissa (2024)
The water quality index (WQI) evaluates physical-chemical and microbiological parameters in a multiplicative weighted equation to determine water quality in rivers. The objective of this project was to determine the water quality index (WQI) in the Nagsiche micro-watershed located in the Salcedo canton, province of Cotopaxi. For this purpose, the study area was characterized and three sampling points were established in the parishes of Cusubamba and Panzaleo. The methodology applied was quantitative, subject to the water quality index proposed by the National Sanitation Foundation of the United States (ICA-NSF); based on the sampling technique and respective instruments for water collection, samples were collected at the three points of the Nagsiche micro-watershed. As for the results obtained, the behavior of the state of the riverbed is evident: in the upper basin it recorded an AQI of 60.35, thus giving a category of regular, for the middle basin it provided an AQI of 53.34, classified as regular, and for the lower basin it provided an AQI of 50.36, with a classification of poor. The water quality in the Nagsiche microbasin oscillates in an average of 55.68, in relation to the three sampling zones, for which it provided a categorization as regular due to the variation of activities carried out on the riverbanks. In turn, the parameters established by the ICA-NSF were compared with the current Ecuadorian regulation TULSMA, according to the determined use criteria, where the variability of the micro-watershed was evidenced, reflecting a contamination in the parameters of Dissolved Oxygen, Fecal Coliforms, BOD5, Temperature and Nitrates according to the directed use. Therefore, the water quality is in regular conditions of physical-chemical and microbiological contamination.